Application of Artificial Intelligence in Mechanical Engineering - Mohammed Ridha H Alhakeem; Dirja Nur Ilham (ITScience (Information Technology and Science), 2022)
The use of artificial intelligence (AI) is becoming more prevalent across many industries. Examples include intelligently based control, intelligently based mechanical systems, pattern recognition-based systems, and knowledge processing. Method/Statistical Analysis: In this paper, an extensive review was conducted on the applications of ANN in intelligent mechanical engineering systems, including fault diagnosis in machines, mechanical structure analysis, and geometry modelling of mechanical structures, mechanical design, and its optimization. Findings: The adaptation of artificial neural networks (ANN), particularly in the field of mechanical engineering, is still in its early stages of development. This paper highlights the different ways artificial neural networks (ANNs) are used in intelligent-based systems, as well as the potential for reducing costs and time and obtaining more efficient systems for mechanical-based design and defect detection. Application/Improvements: This work will be improved in the future by adding more AI applications to the design of mechanically based systems.